Modern considerations of myocardial revascularization in coronary chronic total occlusion - D. K. Vasiliev; B. A. Rudenko (Кардиоваскулярная терапия и профилактика)
Coronary chronic total occlusion (CTO) occurs in 16-18,4% of cases according to observational studies and registers. Traditionally, endovascular revascularization methods are considered a less appropriate strategy then drug therapy. The results of studies have shown that incomplete myocardial revascularization after unsuccessful recanalization leads to a worse long-term prognosis. Due to the accumulated experience and new technical equipment, the success rate of coronary recanalization reached 87-95%. It allows more often achieving complete myocardial revascularization and is as a reason for reconsideration and potential switching from conservative approach to active tactics in CTO. In this regard, there is a great need for randomized clinical trials to assess the efficiency of endovascular revascularization in CTO.